WOMEN IN THE BOARDROOM: CONTRIBUTIONS AND CHALLENGE IN MALAYSIAN COMPANIES - Zainal Abidin, Suhaila; Lokman, Norziana; Abdul Rahim, Memiyanty (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Despite recognising the important role of women directors in improving company performance, their representation on corporate boards remains limited, prompting ongoing debate. This study aims to explore the director's understanding of board diversity, its importance, and women directors' contributions and challenges to reveal the reasons behind the underrepresentation of women directors on corporate boards. The theoretical framework of the study is based on the agency, stakeholder, and resource dependency theory. Employing a qualitative research approach, we interviewed six directors from publicly listed Malaysian companies to extract subjective insights into the contributions and challenges associated with women directors in the boardroom. The findings reflect that the concept of gender diversity is generally recognised and valued by the respondents, primarily for reasons related to board effectiveness, representation and regulatory compliance. It also highlights the three key contributions of women directors in terms of stakeholder representation, decision-making, and engagement in CSR, which would result in enhanced company financial performance, good image and sustainability. However, respondents highlighted challenges in identifying suitable female candidates due to industry-specific knowledge gaps and limited talent pool awareness. This study contributes to understanding gender diversity in corporate governance and the complexities surrounding women's representation on corporate boards. It offers valuable insights for future research and organisational practices.